Dangerous animals - Berger, Melvin; Berger, Gilda (New York : Scholastic, 2009)
Presents facts on a variety of dangerous animals, including lions, tigers, grizzly bears, hippopotamuses, hyenas, rattlesnakes, and others, in a true/false format, and includes color photographs.
Includes index.
5.5.
K-3
Keywords: Dangerous animals -- Juvenile literature; Dangerous animals